Vladimir Nabokov and the art of play - Karshan, Thomas. (Oxford English Monographs, 2011)
In a speech given in December 1925, Vladimir Nabokov declared that 'everything in the world plays', including 'love, nature, the arts, and domestic puns.' All of Nabokov's novels contain scenes of games: chess, scrabble, cards, football, croquet, tennis, and boxing, the play of light and the play of thought, the play of language, of forms, and of ideas, children's games, cruel games of exploitation, and erotic play. Thomas Karshan argues that play is Nabokov's signature theme, and that Nabokov'snovels form one of the most sophisticated treatments of play ever achieved. He traces the idea of art as play back to German aesthetics, and shows how Nabokov's aesthetic outlook was formed by various Russian émigré writers who espoused those aesthetics. Karshan then follows Nabokov's exploration of play as subject and style through his whole oeuvre, outlining the relation of play to other important themes such as faith, make-believe, violence, freedom, order, work, Marxism, desire, childhood, art, and scholarship.